CONFLICTIVE GOVERNANCE: THE DISAPPEARING BOUNDARIES OF LOCAL AND GLOBAL GOVERNANCE FOR DEVELOPMENT AND THE CASE OF MEXICO AND EZLN - Cordeiro, Rui Mesquita (Pensamento & Realidade, 2013)
In a first look, the link between governance and conflict may be a little bit diffuse, but one of the ways of defining governance is as conflict management. In this paper, we will discuss the streams about governance and about conflict, such as the Structural Functionalism, the Marxism, and the Rational Choice Theory. Also we will discuss the role of local governance and the role of global governance, for development. With the passage of time, conceptual and geographical boundaries are challenged, and get a little fuzzy, as we discuss the concepts of the disappearing boundaries. This article also contrasts the ideas of governance and conflict management through a mini case study illustrating the relationship between the Mexican government and the Zapatista National Liberation Army (EZLN), in the state of Chiapas, in southern Mexico, in the 1990s.